Thinking through the skin - Ahmed, Sara, 1969-; Stacey, Jackie (Transformations., 2001)
This exciting collection of work from leading feminist scholars including Elspeth Probyn, Penelope Deutscher and Chantal Nadeau engages with and extends the growing feminist literature on this fascinating topic.